Sequential Organ Failure Assessment Score for Prediction of Mortality of Patients With Rhabdomyolysis Following Exertional Heatstroke: A Longitudinal Cohort Study in Southern China - Wu, Ming; Wang, Conglin; Liu, Zheying; Liu, Zhifeng (Frontiers in Medicine, 2021)
Background: Heatstroke is a medical emergency that causes multi-organ injury and death without intervention, but limited data are available on the illness scores in predicting the outcomes of exertional heatstroke (EHS) with rhabdomyolysis (RM). The aim of our study was to investigate the Sequential Organ Failure Assessment (SOFA) score in predicting mortality of patients with RM after EHS. Methods: A retrospective cohort study was performed, which included all patients with EHS admitted into intensive care unit (ICU) of General Hospital of Southern Theatre Command of Peoples Liberation Army from January 2008 to June 2019. RM was defined as creatine kinase (CK) > 1000 U/L. Data including the baseline data at admission, vital organ function indicators and 90-day mortality were reviewed. Results: A total of 176 patients were enrolled, of whom 85 (48.3%) had RM. RM patients had a significantly higher SOFA score (4.0 vs 3.0, P = 0.021), higher occurrence rates of disseminated intravascular coagulation (DIC) (53.1% vs 18.3%, P < 0.001) and acute liver injury (ALI) (98.842.9% vs 46.717.1%, P < 0.001) than non-RM patients. RM was positively correlated with ALI and DIC, with the correlation coefficients were 0.575 0.236, 0.365, respectively. (both P < 0.0010.01). Multivariate logistics analysis showed that SOFA score (OR 1.7, 95%CI 1.1-2.6, P = 0.024) was the risk factor for 90-day mortality in patients with RM after EHS, with the area under curve (AUC) was 0.958 (95% CI 0.908-1.000, P < 0.001), the optimal cutoff was 7.5 point. Conclusions: RM patients with EHS have severe clinical conditions, which often accompanied by DIC or ALI. SOFA score could predict the prognosis of RM patients with EHS. Early treatment strategies based on decreasing SOFA score on admission may be pivotal to reduce the 90-day mortality of patients with EHS.